Is There Any Rukhṣah in Performing Praying During Covid-19? Maqashid Sharia Analysis - Nizam, Syahrul; Asti, Mulham Jaki (Universitas Islam Negeri Alauddin Makassar, 2021)
The application of rukhṣah in prayer during the Covid-19 pandemic requires a deeper understanding so that the application of rukhṣah is truly implemented in accordance with the corridors that have been determined by Islamic law. Researchers found that the application of rukhṣah in prayer has been carried out in all areas affected by the pandemic even though in some areas they did not take rukhṣah in prayer. However, the mind will be able to think well about the problems of society in accordance with the principles of maqashid sharia, so that it still prioritizes taking rukhṣah rather than forcing the will. The policy on easing congregational prayers, eliminating Friday prayers and physical distancing for congregational prayers carried out by the government and the MUI is an effort to prevent the spread of COVID-19 which leads to the achievement of maqashid sharia so that it provides benefits even in an emergency. The research method used is library research and is qualitative in nature. Sources of data used in this study sourced from primary and secondary data. The results of this study are that it is the ability to cover the genitals for children as a form of caution to avoid unwanted things. Keywords:Rukhṣah; Prayer; Covid-19; Maqashid Shariah